2016
DOI: 10.18632/oncotarget.8052
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants ofGADD45A, GADD45BandMAPK14predict platinum-based chemotherapy-induced toxicities in Chinese patients with non-small cell lung cancer

Abstract: The JNK and P38α pathways play a crucial role in tissue homeostasis, apoptosis and autophagy under genotoxic stresses, but it is unclear whether single nucleotide polymorphisms (SNPs) of genes in these pathways play a role in platinum-based chemotherapy-induced toxicities in patients with advanced non-small cell lung cancer (NSCLC). We genotyped 11 selected, independent, potentially functional SNPs of nine genes in the JNK and P38α pathways in 689 patients with advanced NSCLC treated with platinum-combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The rs3804451 SNP is located on the 3′ untranslated region of MAPK14 ( P38a ) and likely to be functional as predicted by SNPInfo [22]. Indeed, in the present study, we showed that the high expression levels of P38a in tumor tissues were associated with the A allele.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The rs3804451 SNP is located on the 3′ untranslated region of MAPK14 ( P38a ) and likely to be functional as predicted by SNPInfo [22]. Indeed, in the present study, we showed that the high expression levels of P38a in tumor tissues were associated with the A allele.…”
Section: Discussionsupporting
confidence: 58%
“…Our previous study demonstrated that carriers of the MAPK14 rs3804451A variant allele had a significantly higher risk for grade 3/4 overall chemotherapy toxicity [22]; nevertheless, the effects of rs3804451GA/AA genotypes on PFS (Figure 3, C and D ) and OS (Figure 3, E and F ) between different toxicity subgroups showed no difference in the present study ( P  = .676 and .090, respectively) (Supplemental Table S8), suggesting that there was a direct effect of the A allele on PFS and OS, which was not mediated by the toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potentially functional SNPs of nine key genes ( i.e ., GADD45A, GADD45B, GADD45G, MAP2K7, MAP2K4, MAP3K4, MAPK8, MAPK9 and MAPK14 ) involved in the JNK and p38α pathways were selected according to the following criteria: ( i ) The minor allele frequency reported in HapMap was ≥5% in Chinese populations; ( ii ) in low linkage disequilibrium (LD) between SNPs by using an r 2 threshold of 0.8; ( iii ) at the two ends of these genes, such as 5′ UTRs, or 3′UTRs, which may be the regulatory regions of the genes; and ( iv ) potentially affect functions as predicted by SNPinfo (http://snpinfo.niehs.nih.gov/snpinfo/snpfunc.htm) such as transcription factor binding site (TFBS) and miRNA binding site activity; positive SNPs that have been previously reported to be associated with acute lung injury and inter‐ventricular septum hypertrophy are also included. As a result, only 11 SNPs could be selected and genotyped by the TaqMan real‐time PCR method with the Sequence Detection Software on an ABI‐Prism 7900 instrument according to the manufacturer's instructions (Applied Biosystems, Foster City, CA) as described previously . Their predicted functions and related information are summarized in Supporting Information Table S1, and those ungenotyped SNPs that are in linkage disequilibrium (LD) with these 11 SNPs are presented in Supporting Information Table S2.…”
Section: Methodsmentioning
confidence: 99%